Gold nanoparticle networks with photoresponsive interparticle spacings - Sidhaye, D. S.; Kashyap, Sudhir; Sastry, M.; Hotha, Srinivas; Bhagavatula L. V. Prasad (Langmuir, 2005)
Photoresponsive gold nanoparticle networks were prepared by functionalizing them with azobenzene derivatives. A network can be formed when a linker molecule constituting the azobenzene moiety suitably derivatized on either side with gold surface sensitive groups such as thiols and amines is added to the nanoparticle solution. It is shown that the interparticle spacing in the networks could be controlled by the reversible trans-cis isomerization of the azobenzene moiety induced by UV and visible light, respectively. The photoinduced variation in the interparticle spacings is inferred by the changes in the optical spectra of the gold nanoparticles which display a red or blue shift in the surface plasmon resonance peak depending on a decrease or increase in the interparticle spacing, respectively. Transmission electron microscopy images are in consonance with the evidence from the optical spectra.

Propargyl glycosides as stable glycosyl donors: anomeric activation and glycoside syntheses - Hotha, Srinivas; Kashyap, Sudhir (Journal of the American Chemical Society, 2006)

Synthesis of C-2 methylene glycosides from C-2 propargyloxymethyl glycals exploiting the alkynophilicity of AuCl3 - Kashyap, Sudhir; Vidadala, Srinivasa Rao; Hotha, Srinivas (Tetrahedron Letters, 2007)
C-2 Methylene glycosides were synthesized from C-2 propargyloxymethyl glycals in a stereoselective manner using a catalytic quantity of AuCl3. The Au-catalyzed reaction was explored using various aglycones. The current protocol enables the preparation of C-2 methylene glycosides, tolerates diverse functional groups and is fast, catalytic and mild. (c) 2007 Elsevier Ltd. All rights reserved.

Dendritic effect of ligand-coated nanoparticles: enhanced apoptotic activity of silica-berberine nanoconjugates - Halimani, Mahantappa; Chandran, S. Prathap; Kashyap, Sudhir; Jadhav, V. M.; Bhagavatula L. V. Prasad; Hotha, Srinivas; Maiti, Souvik (Langmuir, 2009)
We describe the synthesis and biological characterization of a novel prototype, namely, silica nanoconjugates bearing a covalently linked berberine, a plant alkaloid known to have antiproliferative activity. The effect of synthesized nanoconjugates on cell proliferation, the cell cycle profile, and apoptosis in the human cervical carcinoma cell line (HeLa), human hepatocellular liver carcinoma cell line (HepG2), and human embryonic kidney (HEK) 293T cell line has been studied and compared with the results obtained for free berberine. Our results show that all the nanoconjugates display higher antiproliferative activity than free berberine. The ability of these nanoconjugates to inhibit cellular proliferation is mediated by the cell cycle arrest at the G1 phase. Moreover, silica nanoconugates caused selective apoptotic arrest with a higher efficiency than free berberine followed by apoptotic cell death as shown by quantitative fluorescence-activated cell sorting analyses. Efficiency of the nanoconjugates increases upon an increase in the linker chain length, demonstrating the distinct role of the spacer chain that conjugates nanoparticles and ligands. The actual reason to show enhanced efficiency by the nanoconjugates has not been elucidated in the present study; however, we hypothesize that an increase in local concentration due to the confinement of a ligand on the nanosurface (''dendritic'' effect) might have led to the observed effect.